Stepwise Luweero farmer interviews - International Institute of Tropical Agriculture (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Interviews with three Luweero farmers discussing their experience of working with IITA and HRNS and engaging in the Stepwise Luweero demonstration plot pilots.